2008
DOI: 10.1200/jco.2008.16.5704
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes of Patients With Advanced Biliary Tract Cancers Receiving Gemcitabine Plus Capecitabine: A Multicenter, Phase II Trial of the Swiss Group for Clinical Cancer Research

Abstract: Chemotherapy with GemCap is well tolerated and effective and leads to a high CBR rate. Patient-reported outcomes are useful for evaluating the effects of palliative chemotherapy in patients with biliary tract cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 37 publications
1
60
0
Order By: Relevance
“…Traditionally, 5-fluorouracil-based chemotherapy regimen has been used as an adjuvant therapy for biliary tract malignancies including GB cancer [6,9,20,21]. Recently, gemcitabine-, capecitabine, or S-1-based regimens have been tried, and several studies have demonstrated somewhat promising results from GB cancer [22][23][24][25][26]. However, few comparative analyses of treatments between detailed TNM stages of GB cancer have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, 5-fluorouracil-based chemotherapy regimen has been used as an adjuvant therapy for biliary tract malignancies including GB cancer [6,9,20,21]. Recently, gemcitabine-, capecitabine, or S-1-based regimens have been tried, and several studies have demonstrated somewhat promising results from GB cancer [22][23][24][25][26]. However, few comparative analyses of treatments between detailed TNM stages of GB cancer have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…However, no standard chemotherapy regimen for advanced BTC has been established. Several phase II trials with new chemotherapeutic agents, such as gemcitabine (6)(7)(8)(9)(10), capecitabine (11), oxaliplatin (12), or S-1 (13,14) have demonstrated tumor response in ~15-35% of patients treated with single agents, and in 20-40% of patients treated with their combinations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Among them, gemcitabine has shown promising activity against advanced BTC, and has been commonly used for patients with unresectable or recurrent BTC in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, the combination of gemcitabine and cisplatin is considered to be the standard of care for first-line chemotherapy for patients with advanced or metastatic biliary tract cancers. Examples of other gemcitabine-based or fluoropyrimidine-based (fluorouracil or capecitabine) regimens with demonstrated activity in phase II trials include gemcitabine and cisplatin or oxaliplatin [165][166][167][168][169][170][171][172][173] ; gemcitabine and fluoropyrimidine [174][175][176][177][178][179] ; and fluoropyrimidine and oxaliplatin or cisplatin. [180][181][182][183] Triple-drug chemotherapy regimens also have been shown to be effective in patients with advanced biliary tract cancers, albeit in a very small number of patients.…”
Section: Chemotherapy and Chemoradiation For Advanced Biliary Tract Cmentioning
confidence: 99%